Application of Wordwall Media in Social Studies Learning on Student Learning Outcomes in Elementary Schools: A Systematic Literature Review - Wijayanti, Arlen; Ansori, Yoyo Zakaria; Yonanda, Devi Afriyuni (S&Co Publishing, 2025)
The Wordwall media is a learning aid that can make learning more interactive and engaging. Wordwall is a technology-based learning media that offers interactive features that can be used as a learning aid, making learning more interactive and engaging. Through a review of various existing studies, this article seeks to identify the effectiveness of using Wordwall media and the factors that influence student learning outcomes. The method used in this research is Systematic Literature Review (SLR), by collecting and analyzing data from various relevant sources. The findings indicate that the use of Wordwall media generally has a positive impact on student learning outcomes, increases student engagement, and enriches the learning experience.